Suppression of MR1 by human cytomegalovirus inhibits MAIT cell activation - Ashley, Caroline L.; McSharry, Brian P.; McWilliam, Hamish E. G.; Stanton, Richard J.; Fielding, Ceri A.; Mathias, Rommel A.; Fairlie, David P.; McCluskey, James; Villadangos, Jose A.; Rossjohn, Jamie; Abendroth, Allison; Slobedman, Barry (Frontiers in Immunology, 2023)
The antigen presentation molecule MHC class I related protein-1 (MR1) is best characterized by its ability to present bacterially derived metabolites of vitamin B2 biosynthesis to mucosal-associated invariant T-cells (MAIT cells). This immune axis is less well characterized in the context of viral infection. Human cytomegalovirus (HCMV) encodes hundreds of proteins, some of which regulate the expression of antigen presentation molecules. However the ability of this virus to regulate the MR1:MAIT TCR axis has not been studied in detail. Here we demonstrate that HCMV infection efficiently suppresses MR1 surface expression and reduces total MR1 protein levels. Expression of the viral glycoprotein gpUS9 in isolation could reduce both cell surface and total MR1 levels, with analysis of a specific US9 HCMV deletion mutant suggesting that the virus can target MR1 using multiple mechanisms. Functional assays with primary MAIT cells demonstrated the ability of HCMV infection to inhibit bacterially driven, MR1-dependent activation using both neutralizing antibodies and engineered MR1 knockout cells. Together, this study identifies a strategy encoded by HCMV to disrupt the MR1:MAIT cell axis.